Pentingnya Manajemen Data Pengeboran Untuk Meningkatkan Operasi Pengeboran Panas Bumi - Daniel Adityatama; Rizky Mahardhika; Dorman Purba; Farhan Muhammad; Riviani Kusumawardani; Ribka Asokawaty (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
Drilling is one of the major cost components in geothermal exploration and development. Effective and cost-efficient drilling significantly contribute to the success of geothermal development. Key factors in reducing drilling costs are optimising operations, utilising manpower to its fullest potential, and also benchmarking with other drilling activities to evaluate one’s performance objectively. This is possible if the information regarding the previous drilling activities is stored and easily gathered and analysed before making plans for the drilling campaign. The importance of drilling data analysis and drilling data management have been a subject of study and discussion since the 1980s, but it is still not that common in geothermal drilling, especially in Indonesia. The purpose of this paper is to summarise the definition and examples of drilling data management in a more well-established industry such as oil and gas from various studies in the past, assess the advantages of having a proper drilling database or data management system, and how can the data be used for potentially improving future drilling operation. A case study of converting legacy data from previous drilling campaign of two geothermal fields in Java into a database is also discussed to demonstrate how legacy drilling data can be used to evaluate drilling performance.